Syntheses, Electrochemical, Linear Optical, and Cubic Nonlinear Optical Properties of Ruthenium–Alkynyl‐Functionalized Oligo(phenylenevinylene) Stars1. Issue 8 (3rd July 2015) - Chen, Zhiwei; Jeffery, Christopher J.; Morshedi, Mahbod; Moxey, Graeme J.; Barlow, Adam; Yang, Xinwei; Babgi, Bandar A.; Dalton, Gulliver T.; Randles, Michael D.; Smith, Matthew K.; Zhang, Chi; Samoc, Marek; et al.
Abstract The syntheses of trans‐[Ru(C≡CC6H4‐4‐CHO)(C≡CC6H4‐4‐R)(dppe)2] (R=H (9 a), NO2 (9 b), CHO (9 c), C≡CC6H3‐3, 5‐Et2 (9 d), (E)‐CHCHC6H4‐4‐tBu (9 e); dppe=1, 2‐bis(diphenylphosphino)ethane), trans‐[Ru(C≡CC6H4‐4‐R)Cl(dppe)2] (R=C≡CC6H3‐3, 5‐Et2 (11 a), (E)‐CHCHC6H4‐4‐tBu (11 b), (E)‐CHCHC6H4‐4‐NO2 (11 c)), 1, 2, 4, 5‐{trans‐[(dppe)2(RC6H4C≡C)Ru{C≡CC6H4‐4‐(E)‐CHCH}]}4C6H2 (R=H (14 a), C≡CC6H3‐3, 5‐Et2 (14 b), (E)‐CHCHC6H4‐4‐tBu (14 c)), 1‐I‐3, 5‐{trans‐[(L2)2(R)Ru{C≡CC6H4‐4‐(E)‐CHCH}]}2C6H3 (L2=1, 1‐bis(diphenylphosphino)methane (dppm)), R=Cl (15 a); L2=dppe, R=C≡CPh (15 b), R=C≡CC6H4‐4‐NO2 (15 c)), 1‐Me3SiC≡C‐3, 5‐{trans‐[(L2)2(R)Ru{C≡CC6H4‐4‐(E)‐CHCH}]}2C6H3 (L2=dppm, R=Cl (16 a); L2=dppe, R=C≡CPh (16 b)), 1‐HC≡C‐3, 5‐{trans‐[(dppe)2(R)Ru{C≡CC6H4‐4‐(E)‐CHCH}]}2C6H3 (R=Cl (17 a), R=C≡CPh (17 b)), and 1, 3, 5‐{trans‐[(dppe)2(3, 5‐R2‐C6H3C≡C)Ru{C≡CC6H4‐4‐(E)‐CHCH}]}3C6H3 (R=(E)‐CHCHC6H4‐4‐C≡C‐trans‐[Ru(C≡CPh)(dppe)2] (18)) are reported together with those of the precursor alkynes 1‐RC≡C‐3, 5‐Et2C6H3 (R=SiMe3 (2), H (3), C6H4‐4‐C≡CSiMe3 (5), C6H4‐4‐C≡CH (6)). The identities of 9 c, 9 d, 9 e, 11 a, and trans‐[Ru{C≡CC6H4‐4‐(E)‐CHCHC6H4‐4‐tBu}2(dppe)2] (12 and 12′) were confirmed by single‐crystal X‐ray diffraction studies. The electrochemical properties of 9 a–e, 11 a–b, 14 a–c, 15 a–c, 16 b, 17 a, 17 b, and 18 were assessed by cyclic voltammetry; the studies reveal that potentials for the fully/quasi‐reversible metal‐centered oxidation processes decrease upon introduction of solubilizing alkyl substituents and increase upon increasing acceptor substituent strength; other structural variations have little impact. UV/Vis‐NIR spectroscopic studies on these complexes reveal lowest‐energy metal–ligand charge transfer (MLCT) bands that redshift upon increasing the acceptor substituent strength, blueshift on alkyl incorporation, and gain in intensity on progression from linear to star complexes. Low‐temperature UV/Vis‐NIR spectroelectrochemical studies of 14 a–c show the appearance of an intense low‐energy band at 7400–7900 cm−1 that is redshifted upon π‐system lengthening and alkyl substituent incorporation. The cubic nonlinear optical properties of 9 d, 9 e, 14 a–c, 15 a–c, 16 b, 17 a, b, and 18 were assayed by femtosecond Z‐scan studies at benchmark wavelengths (750 and 800 nm) in the near‐IR region, with nonlinearity increasing upon nitro incorporation; the values for the E‐ene‐linked dendrimers in these studies are much larger than yne‐linked analogues. Compounds 9 d, 9 e, 14 a–c, and 18 were further examined by broad‐spectral‐range femtosecond Z‐scan studies; the cruciform complexes have appreciable multiphoton absorption cross‐sections, with maximal values close to two and three times the wavelength of the linear optical absorption maxima.